Impact of remnant cholesterol on acute ischemic stroke prognosis: a nationwide cohort analysis stratified by non-alcoholic fatty liver disease status - Jiang, Sili; Jin, Aoming; Xing, Wenli; Jing, Jing (Frontiers in Neurology, 2025)
BackgroundRemnant cholesterol (RC) is an emerging non-traditional risk factor for cardiovascular diseases that has garnered increasing attention. In addition, non-alcoholic fatty liver disease (NAFLD) may interact synergistically with RC. This study aimed to evaluate the association between RC and functional outcomes in ischemic stroke patients and to investigate the potential interaction effect between RC and NAFLD.MethodsThis study utilized data from the Third China National Stroke Registry (CNSR-III), which includes ischemic stroke patients monitored for 3 months post-stroke onset. RC was calculated by subtracting both low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) from total cholesterol. Poor functional outcomes were defined as a modified Rankin Scale (mRS) score of 3–6 at the 3-month follow-up. Multivariable logistic regression analyses were conducted to determine the association between RC and functional outcomes. Interaction effect analysis was performed to investigate how NAFLD modifies the relationship between RC and prognosis.ResultsAmong the 7, 234 participants, the mean age was 62.96 ± 11.44 years and 4,572 (63.2%) were male individuals. Compared to the lowest quartile of RC (Q1), the highest quartile of the RC (Q4) was associated with a lower risk of poor functional outcomes (OR: 0.98, 95% CI: 0.96–1.00). Meanwhile, we observed a similar relationship between RC and poor functional outcomes in patients with NAFLD (OR: 0.96, 95% CI: 0.93–0.99); however, in those without NAFLD, there was no significant association between RC and poor functional outcomes.ConclusionWe found an inverse relationship between RC levels and poor functional outcomes in patients with ischemic stroke, which was influenced by NAFLD. Future studies are needed to determine the optimal target levels of RC in NAFLD patients.